2022
DOI: 10.3390/oxygen2030018
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Reactive Oxygen Species in Vascular Complications of Diabetes: Therapeutic Properties of Medicinal Plants and Food

Abstract: The rising prevalence of chronic metabolic disorders, such as obesity and type 2 diabetes, most notably associated with cardiovascular diseases, has emerged as a major global health concern. Reactive oxygen species (ROS) play physiological functions by maintaining normal cellular redox signaling. By contrast, a disturbed balance occurring between ROS production and detoxification of reactive intermediates results in excessive oxidative stress. Oxidative stress is a critical mediator of endothelial dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 215 publications
1
16
0
Order By: Relevance
“…It is well known that ROS plays a crucial role in vascular complications in diabetes. 39 We herein showed that the ROS level was elevated in aortas from DIO mice and in HG-induced RAECs and ginsenoside Rk1 significantly suppressed ROS production. Ginsenoside Rk1 upregulated the expression of Nrf2 and HO-1, implying the role of Nrf2/HO-1 signaling in its anti-oxidative effect.…”
Section: Discussionmentioning
confidence: 69%
“…It is well known that ROS plays a crucial role in vascular complications in diabetes. 39 We herein showed that the ROS level was elevated in aortas from DIO mice and in HG-induced RAECs and ginsenoside Rk1 significantly suppressed ROS production. Ginsenoside Rk1 upregulated the expression of Nrf2 and HO-1, implying the role of Nrf2/HO-1 signaling in its anti-oxidative effect.…”
Section: Discussionmentioning
confidence: 69%
“…For example, the detection of reactive oxygen species (ROS) found in plants and mammals with EPR, which can reveal types and quantities of ROS, provides crucial findings for the interaction between ROSs and pathogens [1][2][3] . The application of ROS detection stretches to tumor 4 , cancer 5 and diabetes studies 6 . Another stream for EPR spectroscopy in the junction of spin trapping and spin labeling creates a powerful tool to reveal the structure and the conformational dynamics of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, smoking increases cholesterol, LDL, and triglycerides, but decreases HDL [ 3 ]. The status of diabetes increases the level of oxygen radicals and reduces the level and bioavailability of NO, which decreases the elasticity and narrowing of blood vessels [ 4 ].…”
Section: Introductionmentioning
confidence: 99%